2019
DOI: 10.31616/asj.2018.0191
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Normal Trends of Serum Creatine Kinase Levels Following Spinal Surgery

Abstract: Study Design Prospective, prognostic study, level II evidence. Purpose To define the normal change in the creatine kinase (CK) levels in patients undergoing prone or supine lumbar or cervical spine surgery and to determine if positioning influences the postoperative changes in the CK levels. Overview of Literature Spine surgery is one of the most commonly performed and fastest growing areas of surgery in the United States. Thus, the various p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The few existing reports on managing patients with VLCADD recommend strict intraoperative monitoring of glucose and serum CK levels along with continuous glucose infusions to prevent hypoglycemia [ 12 , 14 ]. Utilizing this strategy, glucose levels ranged from 140 to 200 mg/dL intraoperatively with no significant elevations of CK levels beyond what is expected after a major spine surgery [ 15 ]. Had signs of rhabdomyolysis been evident, we would have decreased surgical stress by increasing our anesthetics, transfusing blood products or increasing energy supply through glucose administration.…”
Section: Discussionmentioning
confidence: 99%
“…The few existing reports on managing patients with VLCADD recommend strict intraoperative monitoring of glucose and serum CK levels along with continuous glucose infusions to prevent hypoglycemia [ 12 , 14 ]. Utilizing this strategy, glucose levels ranged from 140 to 200 mg/dL intraoperatively with no significant elevations of CK levels beyond what is expected after a major spine surgery [ 15 ]. Had signs of rhabdomyolysis been evident, we would have decreased surgical stress by increasing our anesthetics, transfusing blood products or increasing energy supply through glucose administration.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria included age ≥18 years, primary anterior cervical spinal surgery, including anterior cervical discectomy fusion (ACDF) and anterior cervical corpectomy fusion (ACCF). Exclusion criteria included the presence of traumatic injuries, surgical intervention for underlying infection, tumor or pregnancy, muscle injury or eccentric exercise, or a personal history of rhabdomyolysis, [5] all of which could affect CK level before surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that serum CPK levels increased most significantly during lumbar spine fusion surgery but also increased to varying degrees during minimally invasive lumbar spine surgery [17] and generally return to normal levels within a week after surgery [10] . This study showed that on the second day after surgery, the serum CPK contents of the 2 groups were significantly higher than before.…”
Section: Serum Creatine Phosphokinase (Cpk) Content Is a Sensitive Inmentioning
confidence: 96%
“…The content of serum CPK [10] was detected on the second postoperative day. The differences in perioperative indexes, such as operation time, intraoperative bleeding, incision length, number of X-ray fluoroscopies during surgery, length of hospital stay, and recurrence after 1 year (secondary operation) were observed.…”
Section: Creatine Phosphokinasementioning
confidence: 99%